Vasohibin 1 selectively regulates secondary sprouting and lymphangiogenesis in the zebrafish trunk - de Oliveira, Marta Bastos (Development, 2021)
Previous studies have shown that Vasohibin 1 (Vash1) is stimulated by VEGFs in endothelial cells and that its overexpression interferes with angiogenesis in vivo. Recently, Vash1 was found to mediate tubulin detyrosination, a post-translational modification that is implicated in many cell functions, such as cell division. Here, we used the zebrafish embryo to investigate the cellular and subcellular mechanisms of Vash1 on endothelial microtubules during formation of the trunk vasculature. We show that microtubules within venous-derived secondary sprouts are strongly and selectively detyrosinated in comparison with other endothelial cells, and that this difference is lost upon vash1 knockdown. Vash1 depletion in zebrafish specifically affected secondary sprouting from the posterior cardinal vein, increasing endothelial cell divisions and cell number in the sprouts. We show that altering secondary sprout numbers and structure upon Vash1 depletion leads to defective lymphatic vessel formation and ectopic lymphatic progenitor specification in the zebrafish trunk.